Anxiety and Depression as Co-morbidities in Patients with Primary Headache - Kafle, B; Bagale, Y; Dhungana, M (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Headache is a common neurological disorder and psychiatric comorbidity is very common in primary headache in which anxiety and depression is more common. Data of patients presenting with primary headache and psychiatric comorbidity is scanty in Nepal. The aim of the study was to study the socio-demographic and clinical profile of patients with primary headache, and to study the frequency and pattern of anxiety and depression as comorbidities among these patients. Material and Method: The study was done at the headache clinic in the Department of Psychiatry at Devdaha Medical College and Research Institute, Rupandehi, Nepal. All out-patients attending our clinic over a period of six months (January 2017-June 2017) with a diagnosis of primary headache were included in the present study. Demographic and clinical profiles of these patients were noted in a specially designed socio-demographic and clinical data sheets prepared for the present study. Results: Among the total patients (N=150), 86 (57.3%) were in the age group 20-39 years. Majority 118 (78.7%) cases were female while 32 (21.3%) cases were male patients. 69.3% cases had migraine headache and 28.7%cases had tension type headache. Comorbid psychiatric illness was present in 80 (53.33%) cases among which Anxiety disorder was the most common diagnostic category (31.3%) followed by depressive disorders (22.0%). Conclusion: Anxiety and depression (53.3%) as comorbid disorder is prevalent among those presenting with primary headache and anxiety spectrum disorder was more than depressive disorder. J Psychiatrists’ Association of Nepal Vol. 6, No. 2, 2017